Does Mestizaje Matter in the US? Economic Stratification of Mexican Immigrants - Dávila, Alberto; Mora, Marie T; Stockly, Sue K (American Economic Review, 2011)
Using data from the 2003 New Immigrant Survey, this paper examines whether stratification as reflected by skin shade exists among newly legalized Mexican immigrants in the US. While we do not find evidence that skin color directly related to employment probabilities, complexion appeared to play a role in the likelihood of owning a home, having a bank account, and occupational status. As these outcomes partly reflect immigrants' pre-migration experiences, our findings suggest that the social stratification structure in Mexico might be sustained in the US among Mexican-origin populations.